2010
DOI: 10.1007/s11999-009-1099-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Soaking Allograft in Bisphosphonate: A Pilot Dose-response Study

Abstract: Background Long-term survival of uncemented total joint replacements relies on osseointegration. With reduced bone stock impacted morselized allograft enhances early implant fixation but is subject to resorption. Purpose We therefore asked whether soaking morselized allograft in different concentrations of bisphosphonate before impaction would enhance fixation. Methods In each of 10 dogs, we implanted four unloaded titanium implants surrounded by a 2.5-mm gap into the proximal humerus, two implants in each hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
82
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(95 citation statements)
references
References 25 publications
7
82
3
1
Order By: Relevance
“…However, despite preservation of the allograft, not all studies indicated a positive effect on mechanical implant fixation 11,12 . In an earlier dose-response study 13 , we found that zoledronate caused a dose-dependent inhibition of the resorption of bone allograft. At higher doses, bone formation was blocked, whereas at the lowest dose allograft resorption was delayed without impairing new bone formation.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…However, despite preservation of the allograft, not all studies indicated a positive effect on mechanical implant fixation 11,12 . In an earlier dose-response study 13 , we found that zoledronate caused a dose-dependent inhibition of the resorption of bone allograft. At higher doses, bone formation was blocked, whereas at the lowest dose allograft resorption was delayed without impairing new bone formation.…”
mentioning
confidence: 68%
“…The treatment may reduce allograft resorption and reduce the risk of mechanical implant failure. Several studies have indicated that bisphosphonate-treated bone allograft is not as readily resorbed as untreated bone allograft [6][7][8][9][10][11][12][13] . However, despite preservation of the allograft, not all studies indicated a positive effect on mechanical implant fixation 11,12 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several in vivo studies have shown that a local delivery of BPs can enhance peri-implant bone density [16,17], implant fixation [18e22], and the repair of bony defects [23,24] in animal models and humans. Furthermore BPs have been shown to preserve bone allografts [25,26] as well as bone sites affected by osteonecrosis [27].…”
Section: Introductionmentioning
confidence: 99%
“…Bisphosphonates do affect the biosynthetic characteristics of osteoblasts 21,22 , suggesting that there may be alterations in the extracellular matrix as a consequence of use. Recently, it has been found that the addition of bisphosphonates to implanted allograft bone affects the rate of allograft resorption and can affect the success of implants used with allograft 23,24 . Demineralized bone matrix is commonly used as a bone graft substitute, either alone or to supplement an osteoconductive material, because of its osteoinductive properties.…”
mentioning
confidence: 99%